Analyzing consumer-based brand equity on Facebook: the impact of brand gender - Azar, Salim L. (2017)
In recent years, Facebook and other social media have become key players in branding activities. However, empirical research is still needed about the way in which consumer-based brand equity is created on social media. The purpose of this paper is to study the relationship between masculine and feminine brand personality and brand equity, on Facebook, and to analyze the mediating role of consumer-brand engagement and brand love on this relationship. Data were collected using an online survey with 614 valid responses. The hypotheses were tested using structural equation modeling. Results support 7 of the 11 hypotheses with significant relationship between analyzed constructs. This study confirms the advantages of a clear gender positioning and extends prior research by suggesting that brands with a strong brand gender identity will encourage brand love. Results also highlight that brand love has a mediating role on the relationship between brand gender and overall brand equity.